Correlation between Socio-Economic Characteristics and Housing Quality of Residential Neighbourhoods in Akure, Southwest Nigeria - Adewale Mukhtar Olayiwola; Olayinka Akinsumbo Ajala (Journal of Contemporary Urban Affairs, 2022)
There is a general paucity of explanations for the emerging social and spatial changes in the pattern and socio-economic traits of urban residential housing units in Nigeria. Hence, this study examined the spatial pattern of residential neighbourhoods; assessed the quality of residential housing units; and evaluated the correlation between the socio-economic position of respondents and housing quality in Akure, Nigeria. Data were derived from the household questionnaire, remotely sensed data (Landsat 8 OLI/TIR, 2021), a Google Earth map, a Street Map of Akure Township, and personal observations. The study adopted a step-wise sampling technique to select 383 samples from 139,069 heads of households in Akure in 2021. Data were analysed using percentage distribution, Pearson Correlation Coefficient, and t-test. Results indicated varying housing qualities across three residential zones in Akure, Nigeria; houses in the low-density residential areas were of better quality than the other residential zones. The quality of houses occupied was influenced by the type of occupation, level of education and average annual income of residents. The study concluded that inadequate housing facilities are fundamental to the observed deteriorating housing qualities in the study area. Therefore, the study suggested improvement of the existing infrastructures and the provision of new ones in the study area. The main contribution of this study is to proffer solutions for a sustainable housing delivery system to facilitate a better quality of life in Nigerian urban centres.